Valsalva Retinopathy in Pregnancy: A Case Report and Review of the Literature - Zhou B; Sarwar F; Ashkenazy N (International Medical Case Reports Journal, 2025)
Brenda Zhou, Faiza Sarwar, Noy Ashkenazy Department of Ophthalmology, UT Southwestern Medical Center, Dallas, TX, USACorrespondence: Noy Ashkenazy, Department of Ophthalmology, UT Southwestern Medical Center, 5323 Harry Hines Blvd., Dallas, TX, USA, Tel +1 214-645-0950, Fax +1 214-645-9912, Email noy.ashkenazy@utsouthwestern.eduAbstract: The current case report and literature review evaluate the management and optimal mode of delivery for Valsalva retinopathy in pregnancy. A 30-year-old primigravid female was discussed presenting with Valsalva retinopathy in the left eye at 35 weeks of gestation after dry heaving with a visual acuity of 20/200. Four weeks after cesarean-section, she had worse central vision and improving residual hemorrhage. A literature review of 25 Valsalva retinopathy cases showed all patients treated with laser posterior hyaloidotomy or pars plana vitrectomy achieved complete resolution (median of 1.5 weeks, p = 0.08), compared to 67% of untreated eyes (median of 5 months, p = 0.08). Average final visual acuity was 20/30 for the treated and untreated cohorts. Intervention may result in faster recovery time but with similar final visual acuity. Four (15%) cases of Valsalva retinopathy were incited by vaginal delivery. However, neither vaginal delivery nor cesarean section resulted in recurrence/worsening of premacular hemorrhage. These findings may help guide treatment of challenging Valsalva retinopathy cases in pregnancy.Keywords: valsalva, retinopathy, hemorrhage, pregnancy, retina, spontaneous vaginal delivery, cesarean section